Nursing diagnoses and interventions regarding the quality of life of of people living with HIV: integrative review (Research, Society and Development, 2021)
Introduction: HIV, Human Immunodeficiency Virus, has become a major pandemic and one of the most serious public health problems worldwide. Due to its chronicity, it has become something that people need to live with throughout their lives, influencing the quality of life of these people. Objective: To identify information in the national literature on the quality of life of people living with HIV and to list the main nursing diagnoses and interventions related to improving the quality of life of these individuals. Method: Integrative literature review, with consultation in the libraries and databases Scientific Electronic Library Online (SciELO), Nursing Database (BDENF) and Latin American and Caribbean Literature on Health Sciences (LILACS). Results: 24 articles were chosen to compose the results. The domains with the most affected QL from the speeches were: concern with confidentiality, relationship with the environment, psychological domain, independence, and spirituality. The diagnoses and nursing interventions tried to meet them. Final Considerations: The nurse should appropriate the Nursing Process and act according to the specific health needs of the patient at the time, providing active listening and welcoming, and also being a promoter of health education actions, to reduce injuries and provide greater acceptance of the diagnosis.